An isothermal CRISPR- based lateral flow assay for detection of Neisseria meningitidis - Dao Thi Huyen; Julien Reboud; Dao Thanh Quyen; Jonathan M. Cooper; Thirumalaisamy P. Velavan; Ngo Tat Trung; Le Huu Song (BMC, 2024)
Abstract Background Neisseria meningitidis can cause life-threatening meningococcal meningitis and meningococcemia. Old standard microbiological results from CSF/blood cultures are time consuming. This study aimed to combine the sensitivity of loop-mediated isothermal nucleic acid amplification (LAMP) with the specificity of CRISPR/Cas12a cleavage to demonstrate a reliable diagnostic assay for rapid detection of N. meningitidis. Methods A total of n = 139 samples were collected from patients with suspected meningococcal disease and were used for evaluation. The extracted DNA was subjected to qualitative real-time PCR, targeting capsular transporter gene (ctrA) of N. meningitidis. LAMP-specific primer pairs, also targeting the ctrA, were designed and the LAMP products were subjected to CRISPR/Cas12 cleavage reaction. the readout was on a lateral flow strip. Sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) of LAMP-CRISPR/Cas was compared with real-time PCR assays. The limit of detection (LOD) was established with serial dilutions of the target N. meningitidis DNA and calculated by Probit regression analysis. Results Six LAMP assay-specific primers were developed targeting the ctrA gene of N. meningitidis, which is conserved in all meningococcal serogroups. The LAMP primers did not amplify DNA from other bacterial DNA tested, showing 100% specificity. The use of 0.4 M betaine increased the sensitivity and stability of the reaction. LAMP-CRISPR/Cas detected meningococcal serogroups (B, C, W). The assay showed no cross-reactivity and was specific for N. meningitidis. The LOD was 74 (95% CI: 47-311) N. meningitidis copies. The LAMP-CRISPR/Cas performed well compared to the gold standard. In the 139 samples from suspected patients, the sensitivity and specificity of the test were 91% and 99% respectively. Conclusion This developed and optimized method can complement for the available gold standard for the timely diagnosis of meningococcal meningitis and meningococcemia.